PENGARUH ETHICAL LEADERSHIP DALAM MENCIPTAKAN WORK ENGAGEMENT KARYAWAN - Wijaya, Shierli (Jurnal Bina Manajemen, 2023)
The purpose of this study is to understand the importance of ethical leadership on employee work engagement. The success of an organization or company can never be separated from the role of the leader who regulates and manages the resources and employees they have. The criteria for a good leader are not only seen from their intellectual abilities or far-reaching vision and mission, but also from their integrity, fairness and loyalty to the company and work team they lead.. Ethical leadership is the attitude of a leader who is in a certain management position, who has a role in introducing ethics and norms in every action and relationship with colleagues in the company. This leadership greatly influences employee engagement, because with a leader who has ethics and morals, employees will be more enthusiastic and have a strong desire to help the company achieve its goals. In the end, employee engagement will create good performance so that the company's performance will also increase.